Role of 2-Methoxyestradiol, an Endogenous Estrogen Metabolite, in Health and Disease - Orihuela-Diaz, P; Reuquen-Lopez, P; Diaz-Saldivar, P (Bentham Science Publishers B.V., 2015)
Estradiol (E2) is a steroid hormone whose physiological actions are mainly mediated by its interaction with intracellular estrogen receptors (ER) leading to modification on the mRNA and protein synthesis in its target cells. However, estrogens can also activate several intracellular signal transduction cascades by non-genomic mechanisms. Estrogens must be inactivated and removed from blood through its conversion to soluble compounds with an apparent low estrogenic activity and decreased affinity for ER. In this context, 2-methoxyestradiol (2ME2) is generated by a sequential hydroxylation of E2 via the enzyme cytochrome P450 isoform 1A1 to produce 2-hydroxyestradiol (2OHE2) followed by a conjugation reaction catalyzed by the enzyme Catechol-O-Methyltransferase generating 2ME2 from 2OHE2. Recent evidence indicates that physiological concentration of 2ME2 may regulate several biological processes while high concentrations of this metabolite may induce pathophysiological alterations in several tissues. In the last years, 2ME2 has also been described as a promising anticancer drug although its cellular and molecular mechanisms are still being disclosed. Herein, we will review the available literature concerning the role of 2ME2 in health and disease. We will focus on to describing the intracellular mechanisms by which 2ME2 exerts its effects on reproductive and non-reproductive tissues. The promising anticancer effects of 2ME2 and its synthetic derivatives will also be discussed. Finally, a group of 2ME2-target genes that could be used as biomarkers of 2ME2 under physiological or pathophysiological conditions will be reviewed. © 2015 Bentham Science Publishers.